Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae) - Mifsud, David; Daccordi, Mauro (Zootaxa, 2019)
Colaphellus palaestinus Achard, an alien invasive species is here reported for the first time for Europe. It was found for the first time in Malta in November 2017, and the year after thousands of individuals were observed in Malta with many photographs posted in social media and local news. Global distribution of this species and information on closely related species is also provided here. Colaphellus zarudnyi Medvedev is probably a synonym of C. palaestinus.